Spatial organizations of urban mosques in Klang Valley, Malaysia: case studies / Zamnah Nusi - Nusi, Zamnah (Institute of Graduate Studies, 2017)
Klang Valley is the most populated region in Malaysia so the development of the urban mosques in the region has grown rapidly as to serve the Muslim communities and at the same time to reciprocate with the increase of the Muslim population in the region. Observations on the urban mosques in the city centres like Kuala Lumpur and its peripherals especially during the Friday congregations noted to be overflow every time. They are mostly multi-leveled structures due to the limited plot of the urbanism characteristics. To date there is no study recorded on the spatial organizations and activities of urban mosques in Malaysia. The research problems are to investigate whether such urban mosques spatial organizations are designed according to the guidelines from the Al Quran and Sunnahs; equipped with ancillary spaces for services and activities; which needs proper management of the utilization of the spaces and the maintenance of the buildings. The design of the spaces at the mosques is bounded by the spatial organization which needs to be observed by the managements and the designers of the mosques. At the same time, the local communities’ religious and social needs are to be addressed accordingly in order to build better Muslim communities.